2013
DOI: 10.1890/12-1329.1
|View full text |Cite
|
Sign up to set email alerts
|

Emergent fungal entomopathogen does not alter density dependence in a viral competitor

Abstract: Abstract. Population cycles in forest Lepidoptera often result from recurring densitydependent epizootics of entomopathogens. While these systems are typically dominated by a single pathogen species, insects are often infected by multiple pathogens, yet little is known how pathogens interact to affect host dynamics. The apparent invasion of northeastern North America by the fungal entomopathogen Entomophaga maimaiga some time prior to 1989 provides a unique opportunity to evaluate such interactions. Prior to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…This positive relation to density is what we would expect for LdMNPV [55], and has also been found for E. maimaiga in some studies [27,56], but is not always the case (e.g. [35]), probably because environmental conditions also impact E. maimaiga infection [57] and can restrict density-related responses.…”
Section: (B) Associations With Host Densitysupporting
confidence: 86%
See 1 more Smart Citation
“…This positive relation to density is what we would expect for LdMNPV [55], and has also been found for E. maimaiga in some studies [27,56], but is not always the case (e.g. [35]), probably because environmental conditions also impact E. maimaiga infection [57] and can restrict density-related responses.…”
Section: (B) Associations With Host Densitysupporting
confidence: 86%
“…In central Pennsylvania (PA) (Centre and Huntingdon Counties), at nine ca 7 ha forested sites larvae were sampled every 4-7 days. At these sites, sampling generally began 5-9 June when fourth instars were first seen and ended 22-26 June when pupation had begun [35]. An attempt was made to collect at least 50 larvae per sample date although occasionally populations were too sparse, but at least 18 larvae were taken per visit.…”
Section: (B) Study Sites and Samplingmentioning
confidence: 99%
“…Although these results are consistent with prior investigations of LdNPVinduced mortality McManus and Csóka 2007), previous studies have produced mixed results regarding the density dependence of mortality due to E. maimaiga. In a study conducted on a smaller spatial scale, Liebhold et al (2013) found that E. maimaiga-induced mortality was density independent across sites and three years. A literature review reported that, while density independence was more common (Hajek 1999), E. maimaiga infection was occasionally positively associated with spatial variation in host density (Weseloh and Andreadis 1992).…”
Section: Discussionmentioning
confidence: 95%
“…The activity of LdNPV is dependent on host density (Dwyer 1994;Liebhold et al 2013), while E. maimaiga activity has usually Hajek 1999)-but not always (Weseloh and Andreadis 1992)-been reported to be density independent. Entomophaga maimaiga and LdNPV can co-infect hosts (Malakar et al 1999) and are frequently both present in higher density L. dispar populations (AEH, unpublished data; Reilly et al 2014).…”
Section: Study Systemmentioning
confidence: 99%
“…The first is the mortality induced by natural enemies such as predators (Dwyer et al, 2004;Elkinton et al, 1996), parasitoids (Berryman, 1996;Baltensweiler and Rubli, 1999;Ruohomäki et al, 2000;Turchin et al, 2003) and pathogens (Anderson and May, 1980;Myers, 1993;Liebhold et al, 2013;Elderd et al, 2013). At least 18 parasitoid, 15 predator and 10 pathogen species have been recorded on the different stages of T. pityocampa .…”
Section: Discussionmentioning
confidence: 99%